North Carolina Board of Higher Education Biennial Report, 1967-1969 - North Carolina State Board of Higher Education, Raleigh; North Carolina State Board of Higher Education, Raleigh ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The North Carolina Board of Higher Education was established in 1955 for the purpose of planning and promoting the development of "a sound, vigorous, progressive, and coordinated system of higher education in the State of North Carolina." This report deals with the Board's activities from January 1, 1967 to December 31, 1968, many of which were directed toward the development of a long-range plan for higher education in the State. As background for this plan, 74 studies were undertaken with a focus on the public senior institutions of higher education and the maintenance of strong dual systems of private and public higher education. The 1968 report of the long-range plan dealt with the current adequacy and future needs of higher education in North Carolina. Other activities included planning, research, providing information, assigning the major functions of and determining the types of degrees to be awarded by the state's public senior colleges. The Board also licensed new degree-granting institutions and administered 2 state-wide programs under Title I of the Higher Education Act of 1965 which were directed toward solving community problems in the areas of employment, health, government, and community economic development. A complete chapter of the report is devoted to highlights of several other duties performed by the Board during the 2-year period. (WM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Coordination; Educational Cooperation; Institutional Cooperation; State Programs; Boards of Education; Educational Administration; Higher Education; Program Development; State Colleges; North Carolina Board of Higher Education